Técnicas de representación gráfica axonométrica: los croquis y bloques diagrama - Pellicer Corellano, Francisco (Geographicalia, 2017)
The basis of the strongly attractive axonometric representations are analysed. Some basic techniques destined to the design of volumetric outlines, isometries, oblique elevations with isometric and conical perspectives are developped as well